Merger and acquisitions : airline industry : case between American Airlines and U.S. Airways - Correia, Maria Luísa Freitas (2015)
Not that many inventions are considered to be so life changing as the airplane invention. The airline industry is by far one of the most competitive industries with the highest growth expectations in the world. Nowadays, the sector of air transportation is radically different from what it was prior to 1978. As a consequence, the sector witnessed a massive restructuring with a significant increase in M&A activity. For this reason, the merger between American Airlines and U.S. Airways – two U.S. companies, will be the focus of this dissertation. Taking into account the industry and firm’s conditions and potential, the estimated synergies were valued at $984 million for the first relevant year - 2013, including revenue growth and cost savings. The overall synergies will yield a final equity value of $27.897 million that represents an increase of approximately 71,2%, when compared with the sum of the standalone equity values of both companies. This deal is suggested to be an all-stock deal that leads to the issue of 236 million shares to U.S. Airways shareholders and, as a result, American Airlines stakeholders will own 65% of the new company and the remaining 35% will be owned by U.S. Airways shareholders.